Simulation and Measurement of the Current Density Distribution in Lithium-Ion Batteries by a Multi-Tab Cell Approach. Issue 1 (1st January 2017) - Erhard, S. V.; Osswald, P. J.; Keil, P.; Höffer, E.; Haug, M.; Noel, A.; Wilhelm, J.; Rieger, B.; Schmidt, K.; Kosch, S.; Kindermann, F. M.; Spingler, F.; et al.
Abstract : A single-layered NMC/graphite pouch cell is investigated by means of differential local potential measurements during various operation scenarios. 44 tabs in total allow for a highly resolved potential measurement along the electrodes whilst the single layer configuration guarantees the absence of superimposed thermal gradients. By applying a multi-dimensional model framework to this cell, the current density and SOC distribution are analyzed quantitatively. The study is performed for four C-rates (0.1C, 0.5C, 1C, 2C) at three temperatures (5°C, 25°C, 40°C). The maximum potential drop as well the corresponding SOC deviation are characterized. The results indicate that cell inhomogeneity is positively coupled to temperature, i.e. the lower the temperature, the more uniform the electrodes will be utilized.